2013
DOI: 10.1007/s00395-013-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Non dominant-negative KCNJ2 gene mutations leading to Andersen-Tawil syndrome with an isolated cardiac phenotype

Abstract: Andersen-Tawil syndrome (ATS) is characterized by dysmorphic features, periodic paralyses and abnormal ventricular repolarization. After genotyping a large set of patients with congenital long-QT syndrome, we identified two novel, heterozygous KCNJ2 mutations (p.N318S, p.W322C) located in the C-terminus of the Kir2.1 subunit. These mutations have a different localization than classical ATS mutations which are mostly located at a potential interaction face with the slide helix or at the interface between the C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…In terms of the latter, Kcnj16 −/− mice exhibit no observable behavioral or physical abnormalities. 26 Critically, the findings of this present report support those of Limberg et al, 27 who recently showed that KCNJ2 gene mutations without a dominant negative effect on Kir2.x channels result in an isolated cardiac phenotype, without any of the typical dysmorphic, skeletal muscular, or neurocognitive features typical of ATS. Usually, individuals with ATS are considered to be at lower risk of sudden cardiac death than for other LQT syndromes.…”
supporting
confidence: 86%
“…In terms of the latter, Kcnj16 −/− mice exhibit no observable behavioral or physical abnormalities. 26 Critically, the findings of this present report support those of Limberg et al, 27 who recently showed that KCNJ2 gene mutations without a dominant negative effect on Kir2.x channels result in an isolated cardiac phenotype, without any of the typical dysmorphic, skeletal muscular, or neurocognitive features typical of ATS. Usually, individuals with ATS are considered to be at lower risk of sudden cardiac death than for other LQT syndromes.…”
supporting
confidence: 86%
“…In a large study by Kimura et al that involved 57 ATS probands, C‐peptide region mutations were more common in typical ATS while N‐terminal mutations were more common in those with atypical and cardiac‐only phenotypes . Limberg et al described two mutations involving the C‐terminus that resulted in defective Kir2.1 channel trafficking (W322C mutation) or gating (N318S mutation), and which manifested with a cardiac‐only phenotype . The G144A mutation in our patients involves the selectivity filter region of the gene and results in a gating abnormality of the K + channel .…”
Section: Discussionmentioning
confidence: 64%
“…In a large family with p.Arg67Tyr mutation, periodic paralysis was observed only in men and cardiac abnormalities only in women, with congenital anomalies noted in both sexes. 28 Limberg et al 29 reported that carriers of 2 mutations-p.Asp318Ser and Try322Cys-present only with isolated cardiac manifestations. In a young woman with ATS and p.Arg218Try mutation, Junker et al 9 observed a marked and long-lasting improvement in cardiac and muscular symptoms after taking acetazolamide and amiodarone.…”
Section: Discussionmentioning
confidence: 99%